2019
DOI: 10.1002/slct.201901774
|View full text |Cite
|
Sign up to set email alerts
|

Biodecolorization of Basic Blue 41 using EM based Composts: Isotherm and Kinetics

Abstract: The main goal of this research was to prepare composts from neem (Azadirachta indica A. Juss) leaves and water hyacinth plant for the remediation of Basic Blue 41 (BB41) bearing wastewaters. The process of composting was performed using Effective Microorganisms (EM) for neem tree leaves (EM LC ) and water hyacinth waste (EM WHC ). Through preliminary experiments, for biosorption of BB41, 1.18 mm and 2 g/L were identified as the optimum particle size and compost dosage, respectively. The pH edge experiments rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 40 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…The biosorption process sensitivity to temperature can be used to determine a biosorbent sorption capacity. The impact of temperature on the removal of Basic Blue 41(BB41) through effective microorganism-primarily based total leaf compost was assessed at various temperatures between 25 and 45 °C 47 . The outcomes of the experiment showed that a rise in temperature would result in a greater capacity for dye sorption (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The biosorption process sensitivity to temperature can be used to determine a biosorbent sorption capacity. The impact of temperature on the removal of Basic Blue 41(BB41) through effective microorganism-primarily based total leaf compost was assessed at various temperatures between 25 and 45 °C 47 . The outcomes of the experiment showed that a rise in temperature would result in a greater capacity for dye sorption (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The three different sized 6cm, 8cm and 10cm filled adsorbent column with the flow rate of 3 ml/min was used for the adsorption study [28]. The column study conducted in the room temperature, In the fixed bed column studies, a glass column with an inner diameter of 3 cm and a length of 80 cm was used [29].…”
Section: Column Studymentioning
confidence: 99%
“…The samples were taken after the adsorption research and put in vials that were maintained in region and passed through the mobile phase and stationary phase. [47]. The perfect heavy metal level determined by using graph of GC result.…”
Section: 2gas Chromatographic Studymentioning
confidence: 99%